Dual Targeting by Inhibition of Phosphoinositide-3-Kinase and Mammalian Target of Rapamycin Attenuates the Neuroinflammatory Responses in Murine Hippocampal Cells and Seizures in C57BL/6 Mice - Vyas, Preeti; Tulsawani, Rajkumar; Vohora, Divya (Frontiers in Immunology, 2021)
Emerging evidence suggest association of seizures and inflammation, however, underlying cell signaling mechanisms are still not fully understood. Over-activation of phosphoinositide-3-kinases is associated with both neuroinflammation and seizures. Herein, we speculate PI3K/Akt/mTOR pathway as promising therapeutic target for neuroinflammation-mediated seizures and associated neurodegeneration. Firstly, we cultured HT22 cells for detection of the downstream cell signaling events activated in lipopolysaccharide (LPS)-primed pilocarpine (PILO) model. We then evaluated effects of 7-day treatment of Buparlisib (PI3K inhibitor, 25 mg/Kg p.o.), Dactolisib (PI3K/mTOR inhibitor, 25 mg/kg p.o.), and Rapamycin (mTORC1 inhibitor, 10 mg/Kg p.o.) in LPS-primed PILO model of seizures in C57BL/6 mice. LPS priming resulted in enhanced seizure severity and reduced latency. Buparlisib and dactolisib, but not rapamycin, prolonged latency to seizures, reduced neuronal loss while all drugs attenuated seizure severity. Buparlisib and dactolisib further reduced cellular redox, mitochondrial membrane potential, cleaved caspase-3, p53, nuclear integrity, and attenuated NF-κB, IL-1β, IL-6, TNF-α and TGF-1 and TGF-2 signaling both in vitro and in vivo post-PILO and LPS+PILO inductions, however, rapamycin mitigated the same only in the PILO model. Both drugs protected against neuronal cell death demonstrating the contribution of this pathway in the seizure-induced neuronal pyknosis, however rapamycin showed resistance in combination model. Further, LPS and PILO-exposure enhanced pAkt/Akt and phospho-p70S6/total-p70S6 kinase activity, while buparlisib and dactolisib but not rapamycin could reduce it in combination model. Partial rapamycin resistance was observed possibly due to reactivation of pathway by functionally different complex of mTOR viz. mTORC2. Our study substantiated plausible involvement of PI3K mediated apoptotic and inflammatory pathways in LPS-primed PILO induced seizures and provide evidence that its modulation constitutes an anti-inflammatory mechanism by which, seizure inhibitory effects are observed. We showed dual inhibition by dactolisib as promising approach. Targeting this pathway at two nodes at a time may provide new avenues for anti-seizure therapies.